Cane Reed (Costus speciosus) - Freeman, W.C. (My University, 2010)
Description on the back of the postcard: "Cane Reed. Costus speciosus, 8 ft. to 10 ft high, a vigorous plant belonging to the Ginger family, thriving in a damp situations where it is very effective in flower." The image used for this postcard has been reproduced from the colour drawings of W.G. Freeman.
Colour: Coloured (print); Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Angiosperms--Trinidad and Tobago; Costus speciosus